2020
DOI: 10.1159/000508457
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Disseminated Mucormycosis in a Hematological Immunocompromised Patient with Extensive Voriconazole Exposure: A Case Report and Review of the Literature

Abstract: Disseminated mucormycosis is a rare, opportunistic, and aggressive infection typically presenting in immunocompromised patients. Herein, we report a 55-year-old male with a past medical history of Philadelphia-negative B-cell acute lymphoblastic leukemia who presented with a 2-month history of non-painful necrotic ulcers on the nose, knuckles, elbow, foot, and scrotum following 3 months of voriconazole (VRC) exposure in the setting of an unrelated fungal pneumonia. Our case reinforces the virulent and often fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Gastro intestinal (GI) symptoms are uncommon, but rescue is feasible in the most profoundly immunocompromised individuals, due to the large immune tissue present in the GI tract, including cases involving leukemia patients and intestine transplant recipients [37] . The disseminated form of mucormycosis can develop from any original location of infection and exhibit ill-defined symptoms that make diagnosis extremely difficult [38] . A metastatic skin lesion, however, unmistakably indicates widespread mucormycosis and a dismal prognosis [39] .…”
Section: Introductionmentioning
confidence: 99%
“…Gastro intestinal (GI) symptoms are uncommon, but rescue is feasible in the most profoundly immunocompromised individuals, due to the large immune tissue present in the GI tract, including cases involving leukemia patients and intestine transplant recipients [37] . The disseminated form of mucormycosis can develop from any original location of infection and exhibit ill-defined symptoms that make diagnosis extremely difficult [38] . A metastatic skin lesion, however, unmistakably indicates widespread mucormycosis and a dismal prognosis [39] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a case-control observational study demonstrated that voriconazole prophylaxis is a risk factor for mucormycosis [ 2 ]. Besides, voriconazole causes fatal breakthrough mucormycosis in immunocompromised patients with hematologic malignancies [ 3 ]. This evidence strongly advocates that voriconazole is a predisposing factor for mucormycosis.…”
mentioning
confidence: 99%